Screening, identification and tolerance of specific yeast strains for sour cherry fruit wine - YIN Xin, YANG Yuanyuan, YAN Zhuoyang, AN Feng, SHAN Dongqian, CAI Yuliang, HE Ling (Zhongguo niangzao, 2025)
In order to screen specific yeast strains for sour cherry fruit wine, using naturally fermented sour cherry juice as experimental material, the yeast strains were isolated and screened using traditional culture and separation technology in conjunction with morphological observation. The superior yeast strains were subsequently screened by fermentation performance test and ethanol production capacity test, identified by molecular biology technology, and their tolerance was analyzed. The results indicated that a total of 34 yeast strains were isolated and screened from the naturally fermented sour cherry juice. Among them, 6 superior yeast strains exhibiting rapid gas production and high ethanol production ability were screened, and numbered as FC2, FC3, FC11, FC14, FC16 and FC18, respectively. After identification, the strains FC2 and FC11 were identified as Saccharomyces cerevisiae, while the remaining strains were identified as Hanseniaspora uvarum. All 6 strains could tolerance ethanol volume fraction 16, pH 2.6 and glucose mass concentration 400 g/L, and the strains FC2, FC11 and FC16 exhibited superior tolerance compared to strains FC3, FC14 and FC18. These study results could provide some references for sour cherry fruit wine brewing.